2018
DOI: 10.1002/pon.4714
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of patients with haematological cancer on how clinicians meet their information needs: “Managing” information versus “giving” it

Abstract: These findings can be understood using attachment theory, whereby practitioners' careful management of information demonstrates their care for patients, and patients' trust in the practitioner enables them to feel informed. It follows that, when patients do not feel informed, the solution will not necessarily be more information but might be to help patients feel more secure in a caring clinical relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…One explanation is the manner in which the initial questions were used to elicit responses in our focus groups. Contrary to Bensing et al (2011), who explicitly asked their participants to formulate advice for patients and providers, and Atherton et al (2018), who prompted patients to talk about what information they received in the consultation, we asked our participants what they needed to be able to express their concerns. Therefore, we focused our study on support for concern expression and not on information provision.…”
Section: Ated) Interpersonal Communication Interventions Previous Rementioning
confidence: 99%
See 1 more Smart Citation
“…One explanation is the manner in which the initial questions were used to elicit responses in our focus groups. Contrary to Bensing et al (2011), who explicitly asked their participants to formulate advice for patients and providers, and Atherton et al (2018), who prompted patients to talk about what information they received in the consultation, we asked our participants what they needed to be able to express their concerns. Therefore, we focused our study on support for concern expression and not on information provision.…”
Section: Ated) Interpersonal Communication Interventions Previous Rementioning
confidence: 99%
“…First, surprisingly, participants did not suggest that the behaviour of providers should change; the patients seemed to hold themselves responsible for concern expression. However, previous research concluded that patients believed that the responsibility of a successful consultation was held by the provider and the patient (Atherton, Youg, Kalakonda, & Salmon, 2018;Bensing et al, 2011). One explanation is the manner in which the initial questions were used to elicit responses in our focus groups.…”
Section: Ated) Interpersonal Communication Interventions Previous Rementioning
confidence: 99%
“…With respect to the experiences of patients with chronic haematological malignancies, much existing literature is limited by the inclusion of individuals with both indolent and acute subtypes, with no differentiation between the two with respect to findings. Such studies have focused on issues such as information satisfaction, decision-making, and quality of life, as well as physician communication styles; identifying considerable scope for improvement [8][9][10][11][12][13][14]. Several studies have, however, specifically examined patients with chronic blood cancer subtypes in the last decade or so, with a recent survey identifying poorer diagnostic understanding compared to other malignancies [15]; a worrying issue given the link between information satisfaction and improved quality of life in cancer generally [16].…”
Section: Introductionmentioning
confidence: 99%
“…Clinician assessment of individual health literacy (capacity to access, process and interpret information) is therefore an essential component of SDM, as is noted by others. 15 Providing patients with information that is comprehensible, tailored to their needs and which does not overwhelm, 54 can be challenging. Strategies for ‘drip-feeding’ 54 information, are to be preferred to a one-way-flow of information from clinician to patient (‘broadcasting’), which is regarded as suboptimal.…”
Section: Discussionmentioning
confidence: 99%